THE ESSENCE OF PROBLEM-BASED LEARNING (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The article presents the essence and technology of problem-based learning, in the use of which the teacher creates problematic situations and as a result of their resolution, creative acquisition of professional knowledge, skills, abilities and the development of students' thinking abilities occurs.